Fluid accumulation syndrome in sepsis and septic shock: pathophysiology, relevance and treatment—a comprehensive review - Carmen Andrea Pfortmueller; Wojciech Dabrowski; Rob Wise; Niels van Regenmortel; Manu L. N. G. Malbrain (Annals of Intensive Care)
Abstract In this review, we aimed to comprehensively summarize current literature on pathophysiology, relevance, diagnosis and treatment of fluid accumulation in patients with sepsis/septic shock. Fluid accumulation syndrome (FAS) is defined as fluid accumulation (any degree, expressed as percentage from baseline body weight) with new onset organ-failure. Over the years, many studies have described the negative impact of FAS on clinically relevant outcomes. While the relationship between FAS and ICU outcomes is well described, uncertainty exists regarding its diagnosis, monitoring and treatment. A stepwise approach is suggested to prevent and treat FAS in patients with septic shock, including minimizing fluid intake (e.g., by limiting intravenous fluid administration and employing de-escalation whenever possible), limiting sodium and chloride administration, and maximizing fluid output (e.g., with diuretics, or renal replacement therapy). Current literature implies the need for a multi-tier, multi-modal approach to de-resuscitation, combining a restrictive fluid management regime with a standardized early active de-resuscitation, maintenance fluid reduction (avoiding fluid creep) and potentially using physical measures such as compression stockings. Trial registration: Not applicable. Graphical Abstract